Do you have to evaluate the heart of the cirrhotic patients? - Mohammed Hussien Ahmed; Mohammed Said Radwan; Ibrahim Fathi Amer; Hassan Elsayed Elbatea; Shimaa Mahmoud ElSharawy; Salwa Twafic (Journal of the Pakistan Medical Association, 2023)
Objective: To identify patients with occult cardiac dysfunction and its relationship with the severity of liver impairment. Method: This is a Judgment (Purposive) Sampling, cross-sectional study that was conducted at Kafrelsheikh University Hospital, Egypt, from November 2019 to December 2020, and comprised adult patients of either gender with liver cirrhosis. After detailed history, a clinical examination, pathological assessment and cardiac evaluation based on electrocardiogram and echocardiography, the patients were divided into three groups. Patients who had dyspnoea or cyanosis were in group A, those who did not have dyspnoea or cyanosis but had electrocardiogram and echocardiography abnormalities were in group B, and patients who did not have dyspnoea, cyanosis or electrocardiogram and echocardiography abnormalities were in group C. The severity of the liver disease was evaluated using Child-Pugh and Model of End Liver Disease scores. Data was analysed using SPSS 20. Results: Of the 300 patients, 153(51%) were males and 147(49%) were females. The overall mean age was 55.1±5.1 years (range: 20-60 years). There were 58(19.33%) patients in group A, 108(36%) in group B and 134(44.66%) in group C. Group A patients showed higher Child-Pugh and Model of End Liver Disease scores than the other groups (p<0.05). Child-Pugh score >6 and Model of End Liver Disease score >37 yielded the best accuracy for detecting cardiac abnormalities in group B (p<0.05). Conclusion: There were significant cardiac changes in cirrhotic patients. Keywords: Liver cirrhosis, Electrocardiography, Cirrhotic cardiomyopathy, Hyperdynamic circulation